Discovery of β-d-2′-deoxy-2′-α-fluoro-4′-α-cyano-5-aza-7, 9-dideaza adenosine as a potent nucleoside inhibitor of respiratory syncytial virus with excellent selectivity over mitochondrial RNA and DNA polymerases. Issue 12 (15th June 2015) - Clarke, Michael O.; Mackman, Richard; Byun, Daniel; Hui, Hon; Barauskas, Ona; Birkus, Gabriel; Chun, Byoung-Kwon; Doerffler, Edward; Feng, Joy; Karki, Kapil; Lee, Gary; Perron, Michel; et al.
Graphical abstract: Abstract: Novel 4′-substituted β-d -2′-deoxy-2′-α-fluoro (2′d2′F) nucleoside inhibitors of respiratory syncytial virus (RSV) are reported. The introduction of 4′-substitution onto 2′d2′F nucleoside analogs resulted in compounds demonstrating potent cell based RSV inhibition, improved inhibition of the RSV polymerase by the nucleoside triphosphate metabolites, and enhanced selectivity over incorporation by mitochondrial RNA and DNA polymerases. Selectivity over the mitochondrial polymerases was found to be extremely sensitive to the specific 4′-substitution and not readily predictable. Combining the most potent and selective 4′-groups from N -nucleoside analogs onto a 2′d2′F C -nucleoside analog resulted in the identification of β-d -2′-deoxy-2′-α-fluoro-4′-α-cyano-5-aza-7, 9-dideaza adenosine as a promising nucleoside lead for RSV.